Implikasi Obstruction of Justice terhadap Perlindungan Saksi dan Korban dalam Sistem Peradilan Pidana di Indonesia - Haikal, Muhamad Fikri (Lex Journal: Kajian Hukum & Keadilan, 2023)
This article discusses the concept and regulation of Obstruction of Justice in the Indonesian criminal justice system and its implications for the protection of witnesses and victims. The main issues raised are how the concept and regulation of Obstruction of Justice impact witness and victim protection. This research uses a normative juridical method with a legislative and conceptual approach. The results of the study indicate that the criminal act of Obstruction of Justice can hinder fair law enforcement and negatively impact the protection of witnesses and victims. Effective protection is crucial to maintaining the integrity of the criminal justice system.